The Effect of Motivational Counseling Based on Spiritual Values on Improving Learning Behavior of Pesantren Students - Thohir, Mohamad; Setyosari, Punaji; Atmoko, Adi; Hambali, IM; Abdullah, Muhammad Saffuan (Universitas Negeri Padang, 2023)
Understanding behaviour plays a vital role for students in maximising their potential to achieve academic success and reach professional and life objectives. This study aims to assess the impact of motivational coaching rooted on spiritual principles on enhancing the learning behaviour of pesantren students. The study utilised quantitative research with a pretest-posttest control group design. Ten 11th-grade students from Madrasah Aliyah Bilingual - Pesantren Modern Al Amanah Krian Sidoarjo Indonesia, who exhibited low scores on the learning behaviour questionnaire, had motivational counselling treatment as part of the research. This study utilised the Mann-Whitney U test for data analysis. The results show that the Z-score is -3.318 and the Asymp. Sig. (2-tailed) is 0.001, which is less than 0.05, resulting in the rejection of the null hypothesis (H0). Spiritual-based motivational coaching influences the learning behaviour of pesantren pupils. Future research should investigate changes in meeting sessions, populations, and research methodologies in spiritual-based motivational therapy and its impact on students' learning behaviour.